2013
DOI: 10.3182/20130204-3-fr-2033.00085
|View full text |Cite
|
Sign up to set email alerts
|

From PD to Nonlinear Adaptive Depth-Control of a Tethered Autonomous Underwater Vehicle

Abstract: This paper deals with an experimental comparison between a proportional derivative (PD) controller and an adaptive nonlinear state feedback one, both applied on a tethered autonomous underwater vehicle. The aim is to show the behavior of the closed loop system in the nominal case for each of these two controllers, and then to test their robustness towards some parameters changes. The PD on one hand has a good performance for systems with an unknown model. The adaptive control law on the other hand is known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The nonlinear compensation is given in equation (8). The At the end, the proposed model, equation (10), is a linear system with uncertainties.…”
Section: Fig 3 Robust Controller and Nonlinear Compensatormentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear compensation is given in equation (8). The At the end, the proposed model, equation (10), is a linear system with uncertainties.…”
Section: Fig 3 Robust Controller and Nonlinear Compensatormentioning
confidence: 99%
“…In SAUC-E [6] and euRathlon [7] competitions, we concluded that PID yaw controller was less efficient for low mass AUV. Consequently, advanced control algorithms should be involved, such as the adaptive control scheme in [8], robust control scheme in [9] and interval analysis approach in [10]. Note that robust control schemes are shown to be successfully in [11] and [12] for torpedo-shaped AUVs.…”
Section: Introductionmentioning
confidence: 99%
“…In [1] an experimental evaluation of an AMBC is reported during simultaneous motion in the translational DOF. Comparative experimental evaluations of linear controllers, model-based controllers and their adaptive extensions for UV single DOF motion have been reported [13], [25]. In [33] a comparative experimental evaluation in the presence of a common external disturbance for proportional integral derivative control, disturbance observer control and the adaptive extensions of both is reported.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The most basic task of this card is to balance the vehicle with the PID control system by using the data it receives from IMU. The PID control method is a feedback control mechanism commonly used in industrial control systems (Johnson & Moradi, 2005;Maalouf et al, 2013;Shen, Cao, Zhou, Xu, & Gu, 2013). A PID controller calculates an "error" value by taking the difference between the measured value and the desired reference value.…”
Section: Water Vehicles Communication Systemsmentioning
confidence: 99%